KEMAMPUAN GURU MENGELOLA KELAS TERHADAP PROSES PEMBELAJARAN - Ampera, Dina; Rambe, Nana Ronawan; Ihwani, Mohamad; Erlando, Rizki (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
This research was conducted to study how teachers manage the classroom and its impact on the learning process. This research uses qualitative methods, which collect descriptive data in the form of written and spoken words from observations of teacher and student behavior in the classroom. The researcher used purposive sampling technique to obtain the required information. The research subjects were fififth-grade teachers and supporting subjects are students and school principals. The research results show that teachers at MI Terpadu Almadinah have good abilities in managing class V, especially in applying class management principles such as creating a warm and enthusiastic atmosphere, providing challenging and varied material, flexible cooling, emphasizing positive things, and foster self-discipline in students. Teachers are also able to design a positive learning process and physical classroom environment. However, there are still obstacles in using media methods and classroom equipment.